2018
DOI: 10.3847/1538-4357/aacc26
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energetic Particle Events Observed by the PAMELA Mission

Abstract: Corresponding author: Alessandro Bruno alessandro.bruno-1@nasa.gov 2 Bruno et al.Despite the significant progress achieved in recent years, the physical mechanisms underlying the origin of solar energetic particles (SEPs) are still a matter of debate. The complex nature of both particle acceleration and transport poses challenges to developing a universal picture of SEP events that encompasses both the low-energy (from tens of keV to a few hundreds of MeV) observations made by space-based instruments and the G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 98 publications
4
59
0
Order By: Relevance
“…The high‐energy data in the spectrum of the 10 September event suggest the presence of a rollover—albeit with large uncertainties due to the few points and their error bars—similar to that found in the high‐energy SEP observations reported by the PAMELA mission (Bruno et al, ) that may be consistent with the limits of diffusive shock acceleration (see section ). Comparing the fits performed with the Band (blue) and the combined (red curve) functions, we obtain a ∼1.36 value for the ratio of the corresponding reduced χ 2 ( F test).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The high‐energy data in the spectrum of the 10 September event suggest the presence of a rollover—albeit with large uncertainties due to the few points and their error bars—similar to that found in the high‐energy SEP observations reported by the PAMELA mission (Bruno et al, ) that may be consistent with the limits of diffusive shock acceleration (see section ). Comparing the fits performed with the Band (blue) and the combined (red curve) functions, we obtain a ∼1.36 value for the ratio of the corresponding reduced χ 2 ( F test).…”
Section: Resultssupporting
confidence: 79%
“…In general, multiple spectral features can be present at different energies, and the above functional forms hardly reproduce the spectral shapes over the complete energy range of SEPs. In particular, the Band function reasonably describes the SEP spectra below several tens of MeV, but it reduces to a single power‐law extending to infinity for energies much larger than the break energy; consequently, it cannot be used to account for the high‐energy (hundreds of MeV) spectral rollovers recently found in PAMELA observations (Bruno et al, ). In order to reproduce both the low‐energy break and the high‐energy rollover in the SEP spectra, equations and can be combined into Φtotfalse(Efalse)=ΦBandfalse(Efalse)exp()Efalse/Er, that is, a double‐power law (Band) function multiplied by an (E‐R) exponential cutoff.…”
Section: Sep Spectral Analysismentioning
confidence: 99%
“…Mishev, Kocharov, and Usoskin, 2014;Plainaki et al, 2014), however, here we focus on the event-integrated fluence. Most importantly, the event was observed by the PAMELA experiment, which directly measured the SEP integral fluence (Bruno et al, 2018). In Figure 8 we confront the spectra reconstructed here, using different YFs, with that measured directly in space.…”
Section: Gle #71: 17 May 2012mentioning
confidence: 96%
“…One can see that the spectra, reconstructed using the R eff method, are fully consistent with the direct data (gray area) in the spectral shape, but those based on CD00 and Ma16 YFs tend to underestimate the low-energy range of the spectrum. On the other hand the Band-function approx- (Bruno et al, 2018). imation (R18) systematically underestimates, by the factor 2 -3, the fluence in the rigidity range of about 2 GV (energy about 1 GeV).…”
Section: Gle #71: 17 May 2012mentioning
confidence: 97%
“…Cohen & Mewaldt (2018) also found that the particle spectra for proton and other ions in the 2017 September proton). However, Bruno et al (2018) showed that the particle spectra between ∼80 MeV and a few GeV in 26 major SEP events observed by PAMELA are well described by a power law with exponential rollover, with a spectral slope of 2.2 and break energy at ∼170 MeV on average.…”
Section: Discussion On the Double-power-law Feature In Particle Energymentioning
confidence: 97%